Pathophysiology of Status Epilepticus Induced by Pilocarpine - Freitas, R. M.; Oliveira, A. A.; F. Sousa, F. C.; M. Vasconcelos, S. M.; B. Viana, G. S.; F. Fonteles, M. M. (Central Nervous System Agents in Medicinal Chemistry, 2007)
Status epilepticus (SE) is clinically defined as prolonged electrical and clinical seizure activity in which the patient does not regain consciousness to a normal alert state between repeated tonic-clonic attacks. The disorder is a neurological emergency associated with a mortality rate of 10-12% and an even greater morbidity. SE can lead to permanent pathological damage and altered physiological function in certain brain regions and induces major changes in membrane phospholipids, massive increases in arachidonic acid concentrations, diacylglycerol-mediated activation, of protein kinase C, calcium-mediated changes in calmodulin kinase II and possibly generation of free radicals that could play an essential role in the mechanism of oxidative stress involved in neural damage. SE can be characterized by a permanent change in neurotransmitter systems and oxidative stress that it is more facilitated in the brain rather than in other tissues because it contains large quantities of oxidizable lipids and metals. The role of monoamines, amino acid and oxidative stress in pilocarpine- induced SE will be investigated in hippocampus, striatum and frontal cortex of adult rats. The SE studied will be induced by pilocarpine (400mg/kg, s.c.) and the results observed were investigated during acute phase. The data obtained suggests that pilocarpine induced amino acid and oxidative stress changes in brain regions that are similar to the one verified in human temporal lobe epilepsy.
Keywords: oxidative stress